Mackenzie pipeline hearings, Hyatt Regency - Pacific Tribune (photographer) (1976)
Hearings conducted by the Berger Inquiry into the Mackenzie Valley Pipeline opened in Vancouver May 10, 11 and 12 before moving to Calgary. Photograph shows Justice Tom Berger on the far right.